Expression of the toxin‐antitoxin genes yefMLrh, yoeBLrh in human Lactobacillus rhamnosus isolates. (1st April 2015) - Krügel, Hans; Klimina, Ksenia M.; Mrotzek, Grit; Tretyakov, Alexander; Schöfl, Gerhard; Saluz, Hans‐Peter; Brantl, Sabine; Poluektova, Elena U.; Danilenko, Valery N.
<x xml:space="preserve">Abstract</x> Lactobacilli are important microorganisms in various activities, for example, diary products, meat ripening, bread and pickles, but, moreover, are associated directly with human skin and cavities (e.g., mouth, gut, or vagina). Some of them are used as probiotics. Therefore, the molecular biological investigation of these bacteria is important. Earlier we described several toxin antitoxin systems (type II) in lactobacilli. Here, we describe the structure and transcriptional regulation of genes, encoding TA system YefM‐YoeBLrh in three strains of Lactobacillus rhamnosus comparing stationary and exponential growth phases, the influence of stress factors and mRNA stability. The same TA system is responding to physiological and stress conditions differently in related strains. Using primer extension and RLM‐RACE methods we determined three transcription start sites of RNAs in the operon. The promoter region of the operon is preceded by a conserved BOX element occurring at multiple positions in the genomes of L. rhamnosus strains. Downstream of and partially overlapping with the 3′ end of the yoeBLrh toxin gene, a divergently transcribed unexpected RNA was detected.